Poincaré Series of some Hypergraph Algebras - Emtander, E.; Fröberg, R.; Mohammadi, F.; Moradi, S. (MATHEMATICA SCANDINAVICA, 2013)
A hypergraph H=(V,E), where V={x_1,…,x_n} and E2^V defines a hypergraph algebra R_H=k[x_1,…, x_n]/(x_i_1… x_i_k; {i_1,…,i_k}E). All our hypergraphs are d-uniform, i.e., |e_i|=d for all e_iE. We determine the Poincaré series P_R_H(t)=_i=1^∞_kTor_i^R_H(k,k)t^i for some hypergraphs generalizing lines, cycles, and stars. We finish by calculating the graded Betti numbers and the Poincaré series of the graph algebra of the wheel graph.